If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 2x = 2y + 6 Reorder the terms: 5 + 2x = 6 + 2y Solving 5 + 2x = 6 + 2y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 2x = 6 + -5 + 2y Combine like terms: 5 + -5 = 0 0 + 2x = 6 + -5 + 2y 2x = 6 + -5 + 2y Combine like terms: 6 + -5 = 1 2x = 1 + 2y Divide each side by '2'. x = 0.5 + y Simplifying x = 0.5 + y
| 0=48x-16x^2 | | -6(p+4)=-4(-7+8p) | | -x+6=189 | | x^2-14=49 | | (2x)(3x)(4x)= | | x-.02x=31110 | | 37=213-u | | -3.6x+2.2=-15.8 | | 10^(1/2) | | -12=5p-3p | | x+.02x=31110 | | 6In(x+8)-4Inx= | | -12=7n+5n | | 2y^2z*-yz= | | 7y-6=10y | | 17a=8+9a | | x-2/8=x | | 150+7.50x=600 | | 5+4lnx=11 | | 8z+6=6z+4 | | x-2/8 | | 12x=600 | | x^2-12+27=9 | | log(9)3+log(9)5+6log(9)2=0 | | x/.75=.33 | | 2yz*-yz= | | 150+1.75x=600 | | .25x-4+.75x=16+.25-10 | | 144=12t | | 7+6m=63 | | 5a=69 | | 75-1x=1x+5 |